2014
DOI: 10.1097/aud.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Language Structures Used by Kindergartners With Cochlear Implants

Abstract: Objective Listeners use their knowledge of how language is structured to aid speech recognition in everyday communication. When it comes to children with congenital hearing loss severe enough to warrant cochlear implants (CIs), the question arises of whether these children can acquire the language knowledge needed to aid speech recognition, in spite of only having spectrally degraded signals available to them. That question was addressed in the current study. Specifically there were three goals: (1) to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 59 publications
(88 reference statements)
1
22
1
1
Order By: Relevance
“…This finding was consistent with previous studies (Nittrouer, Caldwell, Lowenstein, Tarr, & Holloman, 2012). In contrast to previous studies that reported mean performance levels of −1.5 SD (James, et al, 2008; Nittrouer, et al, 2012; Nittrouer, et al, 2014), the present study found that performance was on average within 1 SD of the mean of the normative population. The enhanced performance of children in the present study may be related to the early age of intervention, the up-to-date hearing technology fitted to the children, and the high-quality hearing service provided by AH, the government-funded national provider of hearing services to all children with hearing loss in Australia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding was consistent with previous studies (Nittrouer, Caldwell, Lowenstein, Tarr, & Holloman, 2012). In contrast to previous studies that reported mean performance levels of −1.5 SD (James, et al, 2008; Nittrouer, et al, 2012; Nittrouer, et al, 2014), the present study found that performance was on average within 1 SD of the mean of the normative population. The enhanced performance of children in the present study may be related to the early age of intervention, the up-to-date hearing technology fitted to the children, and the high-quality hearing service provided by AH, the government-funded national provider of hearing services to all children with hearing loss in Australia.…”
Section: Discussioncontrasting
confidence: 99%
“…This complements the predominately high-frequency information transmitted by the cochlear implant to enhance consonant perception (Ching, 2011; Incerti, Ching, & Hill, 2011). It has also been shown that bimodal experience is beneficial for language development in young children with one or two cochlear implants (Nittrouer & Chapman, 2009; Nittrouer, Sansom, Low, Rice, & Caldwell-Tarr, 2014). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tobey et al (2003) report that phonological coding ability and linguistic competence were both predictive skills for reading and Spencer & Oleson (2008) found that speech production and comprehension skills 48 months after implantation accounted for 59% of the variance in written word comprehension three years later. However, detailed assessment of phonological skills in DHH children has shown that they are still lower than those of hearing peers (Herman et al, 2014;Spencer & Tomblin, 2009); and that the benefits of implant technology are greater for language than for phonological skills (Nittrouer, Sansom, Low, Rice, & Caldwell-Tarr, 2014). Nittrouer et al argue that the signal quality available to CI users makes the acquisition of phonological structure problematic for children in comparison to the learning of grammar and vocabulary.…”
Section: Introductionmentioning
confidence: 99%
“…Prelingually deafened children with cochlear implants often present with difficulties that include performing below grade level on phonological awareness, on sentence comprehension, and on reading (Johnson & Goswami, 2010;Lund, 2016;Nittrouer, Sansom, Low, Rice, & Caldwell-Tarr, 2014). Thus, having a tool to identify early sound processing problems, which may form the foundation for these subsequent difficulties, is both theoretically and clinically beneficial, and there is now substantial evidence that fNIRS can be used to examine a range of issues relevant to the development of early language processing abilities.…”
Section: Fnir S In S Peech Re S E Archmentioning
confidence: 99%